2013
DOI: 10.1063/1.4797468
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary melting in ice

Abstract: We describe an optical scattering study of grain boundary premelting in water ice. Ubiquitous long ranged attractive polarization forces act to suppress grain boundary melting whereas repulsive forces originating in screened Coulomb interactions and classical colligative effects enhance it. The liquid enhancing effects can be manipulated by adding dopant ions to the system. For all measured grain boundaries this leads to increasing premelted film thickness with increasing electrolyte concentration. Although we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…Thus the theoretical treatment predicts that the temperature dependence of the layer thickness varies depending on which interactions are dominating (Wettlaufer, 1999;Dash et al, 2006). As a consequence of these predictions in certain cases thickness can behave non-monotonically with respect to temperature and/or impurity level (Benatov and Wettlaufer, 2004;Thomson, 2010;Thomson et al, 2013).…”
Section: Thermodynamics Of Surface Disordermentioning
confidence: 95%
“…Thus the theoretical treatment predicts that the temperature dependence of the layer thickness varies depending on which interactions are dominating (Wettlaufer, 1999;Dash et al, 2006). As a consequence of these predictions in certain cases thickness can behave non-monotonically with respect to temperature and/or impurity level (Benatov and Wettlaufer, 2004;Thomson, 2010;Thomson et al, 2013).…”
Section: Thermodynamics Of Surface Disordermentioning
confidence: 95%
“…Given that κ depends on d through ρ i , the resulting behavior of the layer thickness as a function of impurity concentration N i and undercooling ΔT can be quite complex as discussed in several studies (Wettlaufer, 1999;Benatov and Wettlaufer, 2004;Thomson et al, 2010;Hansen-Goos and Wettlaufer, 2010). The second contribution to I ðdÞ originates in London dispersion forces or van der Waals forces (Dash et al, 2006;French, 2010).…”
Section: Interfacial Premelting Of Icementioning
confidence: 99%
“…The prime indicates that the n¼0 term carries a weight of 1 2 (see Bergström, 1997;French, 2010 and references therein). The fully retarded DLP theory has been applied to the premelting of ice for the ice/water/vapor (surface melting Elbaum and Schick, 1991), the ice/water/substrate (interfacial melting Wilen et al, 1995), and the ice/water/ice (grain boundary Benatov and Wettlaufer, 2004;Thomson et al, 2010) systems, and it is this latter situation that we focus on here. It is found that the surface melting of ice is incomplete due to the crossover in the relative polarizabilities of ice and water in the ultraviolet.…”
Section: Interfacial Premelting Of Icementioning
confidence: 99%
See 1 more Smart Citation
“…In premelting theory liquid melt evolves from crystalline surfaces as temperature and impurity change in ways that depend sensitively on the magnitude and fall-off of the relevant intermolecular interactions Thomson et al, 2010;Bartels-Rausch et al, 2014). Predicted sensitivities have been experimentally probed and observations confirm the basic theoretical assertions (Elbaum et al, 1993;Thomson et al, 2013). Although, the processes of nucleation and melting are not reversible, in both cases capturing the details requires an intimate understanding of the governing interactions.…”
Section: Discussion and Atmospheric Implicationsmentioning
confidence: 89%